2022
DOI: 10.1002/pon.5890
|View full text |Cite
|
Sign up to set email alerts
|

Intersectionality in cancer care: A systematic review of current research and future directions

Abstract: Objectives The objective of the current review was to synthesize the literature on intersectionality relative to disparities across the cancer care continuum. A model to support future intersectional cancer research was proposed. Methods Web‐based discovery services and discipline‐specific databases were queried for both peer‐reviewed and gray literature. Study screening and data extraction were facilitated through the Covidence software platform. Results Among 497 screened studies, 28 met study inclusion crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 50 publications
(137 reference statements)
0
22
0
Order By: Relevance
“…This notion was confirmed in a recent cross-sectional survey which revealed that 29% of Black sexually diverse (SD) women with breast cancer chose to delay care due to barriers such as past negative healthcare encounters, other priorities or struggles relating to scheduling an appointment [6 ▪ ]. Those Black SD women with breast cancer who engaged in cancer treatment often faced Healthcare Provider (HCP) assumptions, mistreatment and felt misunderstood during their care according to a review on the topic [7]. In addition, surveys have revealed that Black SGD prostate cancer survivors are more likely to have a lower health-related quality of life following treatment despite considering covariates [8] and Black and Hispanic SGD cancer survivors were 2 to 3 times more likely to experience depression and poor mental health in comparison with Black and Hispanic heterosexual cancer survivors [9 ▪ ].…”
Section: Resultsmentioning
confidence: 99%
“…This notion was confirmed in a recent cross-sectional survey which revealed that 29% of Black sexually diverse (SD) women with breast cancer chose to delay care due to barriers such as past negative healthcare encounters, other priorities or struggles relating to scheduling an appointment [6 ▪ ]. Those Black SD women with breast cancer who engaged in cancer treatment often faced Healthcare Provider (HCP) assumptions, mistreatment and felt misunderstood during their care according to a review on the topic [7]. In addition, surveys have revealed that Black SGD prostate cancer survivors are more likely to have a lower health-related quality of life following treatment despite considering covariates [8] and Black and Hispanic SGD cancer survivors were 2 to 3 times more likely to experience depression and poor mental health in comparison with Black and Hispanic heterosexual cancer survivors [9 ▪ ].…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, qualitative analytical tools such as intersectionality––describes the impact of multiple social identities (e.g., Black race, female gender, and class) on discrimination and disadvantage, provide a much needed contextual framework 55 . In the setting of surgical disparities based on nSES, frameworks such as intersectionality enables researchers to delve into how social identity that is, race, sexual orientation, socioeconomic status, affects the surgeon−patient relationship, and influences surgical decision making 56,57 …”
Section: Discussionmentioning
confidence: 99%
“…55 In the setting of surgical disparities based on nSES, frameworks such as intersectionality enables researchers to delve into how social identity that is, race, sexual orientation, socioeconomic status, affects the surgeon −patient relationship, and influences surgical decision making. 56,57 The strength of this study is the use of a large collection of population-based central cancer registries. The SEER Program captures information from heterogeneous, diverse geographic areas representing the United States in terms of SES and race and ethnicity.…”
Section: Low Value Surgical Carementioning
confidence: 99%
“…Building in accessibility would mean that each time an adjustment is required for an individual they would not have to go through a formal process asking for accommodations or “reasonable” adjustments. This is important to address the intersectional issues mentioned earlier; not everyone has equal access to diagnosis 37 and the capacity to request accommodations. None of the adjustments suggested below would impair the functioning of a lab for those who are not disabled—to the contrary, they are likely to improve the lab experience for all.…”
Section: Recommendationsmentioning
confidence: 99%